Effectiveness of modified health belief model-based intervention to reduce body mass index for age in overweight junior high school students in Thailand - Waraporn Khumros; Arnond Vorayingyong; Siriluck Suppapitiporn; Thanapoom Rattananupong; Vitool Lohsoonthorn (College of Public Health Sciences, Chulalongkorn University, 2019)
Purpose - The purpose of this paper is to determine the effectiveness of a modified HBM-based intervention to reduce body mass index (BMI) for age in overweight junior high school students. Design/methodology/approach - A cluster-randomized controlled trial was conducted in the first and second years of a junior high school in the center of Thailand. In total, 24 classrooms were randomly assigned to a modified health belief model intervention arm (HBMIA), and 24 classrooms were randomly assigned to a traditional school health education arm (control). In total, 479 students who were overweight (BMI forage = median +1 SD, aged 12-15 years) participated in the study. The HBMIA used the health belief model (HBM) as a motivator for behavioral strategies that included modifying diet and participating in physical activity. BMI, health knowledge and behavior for preventing obesity were recorded at baseline and at six months. A multilevel regression model was performed to calculate mean difference between HBMIA and control group. Findings - The students who participated in the HBMIA showed a decrease in BMI of 1.76 kg/m2, while those who participated in the control showed an increase in BMI of 1.13 kg/m2, with a mean difference of -2.88 kg/m2 (95% CI =-3.01 to -2.75), an improvement in health knowledge (mean difference 27.28; 95% CI =26.15-28.41) and an improvement in health behavior (mean difference 23.54; 95% CI =22.60-24.48). Originality/value - A modified HBM-based intervention to reduce BMI for age is effective in overweight junior high school students.